Biosurfactant synthesis by Pseudomonas aeruginosa LBI isolated from a hydrocarbon-contaminated site - Pirollo, M. P. S. [UNESP]; Mariano, A. P. [UNESP]; Lovaglio, R. B. [UNESP]; Costa, S. G. V. A. O. [UNESP]; Walter, V.; Hausmann, R.; Contiero, Jonas [UNESP] (Blackwell Publishing, 2008)
Aims: Pseudomonas aeruginosa LBI (Industrial Biotechnology Laboratory) was isolated from hydrocarbon-contaminated soil as a potential producer of biosurfactant and evaluated for hydrocarbon biodegradation. The emulsifying power and stability of the product was assessed in the laboratory, simulating water contamination with benzene, toluene, kerosene, diesel oil and crude oil at various concentrations.Methods and Results: Bacteria were grown at 30 degrees C and shaken at 200 rpm for 168 h, with three repetitions. Surface tension, pH and biosurfactant stability were observed in the cell-free broth after 168 h of incubation. The strain was able to produce biosurfactant and grow in all the carbon sources under study, except benzene and toluene. When cultivated in 30% (w/v) diesel oil, the strain produced the highest quantities (9.9 g l(-1)) of biosurfactant. The biosurfactant was capable of emulsifying all the hydrocarbons tested.Conclusion: The results from the present study demonstrate that Ps. aeruginosa LBI can grow in diesel oil, kerosene, crude oil and oil sludge and the biosurfactant produced has potential applications in the bioremediation of hydrocarbon-contaminated sites.Significance and Impact of the Study: Pseudomonas aeruginosa LBI or the biosurfactant it produces can be used in the bioremediation of environmental pollution induced by industrial discharge or accidental hydrocarbon spills.
Keywords: bioremediation; biosurfactant; hydrocarbon; oil sludge; Pseudomonas aeruginosa LBI